Charge Transport and Gradient Doping in Nanostructured Polypyrrole Films for Applications in Photocurrent Generation - Pozzoli, Guilherme L. [UNESP]; Merces, Leandro; Yassitepe, Emre; De Morais, Vitória B.; De Camargo, Davi H. S. [UNESP]; Bufon, Carlos C. Bof [UNESP] (American Chemical Society (ACS), 2020)
The investigation of the charge-transport mechanism across disordered conducting and semiconducting materials is of relevance, considering the applications in modern organic and hybrid electronics. The transition from bulk to nm-thick layers may lead to unexpected physical/chemical properties as the device interfaces do influence the overall charge-carrier conduction. Here, we present an investigation of the electrical transport across vertical heterojunctions having disordered nm-thick films (polypyrrole, PPy) as the active material. The PPy structures are prepared by chemical polymerization from the pyrrole vapor phase, resulting in film thicknesses of a few tens of nanometers. The electrical characteristics of the devices are evaluated as a function of voltage and temperature, and the charge transport is found to be strongly influenced by the presence of trap states at the PPy highest occupied molecular orbital-giving rise to space-charge-limited conduction with exponential distribution of traps. The trapping-state density is calculated, and X-ray photoelectron spectroscopy revealed an increase of disorder and a reduced doping density at the PPy growth interface. As a proof of concept, the PPy films integrated within the as-fabricated vertical heterostructures are applied as photosensitive devices. The observation of photocurrent is correlated to the presence of a gradient in the doping profile (from ca. 27.6 to 17.2% when thickness decreases from 120 to 20 nm). Our findings contribute to the elucidation of the charge-trapping center's origin in the nm-thick PPy films, as well as envision further applications in photoelectrochemistry, solar cells, and water splitting.
Keywords: gradient doping; heterojunction; nanoelectronics; nanomembrane; photocurrent; polymer